Labor Costs and Corporate Investment in Italy - Garcia-Macia, Daniel (IMF Working Papers; Working Paper ;, 2020)
The recovery of private investment in Italy has lagged its euro area peers over the past decade. This paper examines the role of elevated labor costs in hindering the recovery. Specifically, labor costs rose faster than labor productivity prior to the global financial crisis and have remained high since, weighing on firms' profits, capital returns, and thus capacity to invest. Empirical analysis provides evidence for the impact of wages on investment at the sectoral and firm levels. Sectoral wage growth seems unrelated to sectoral productivity growth, but is negatively associated with investment. Firm-level data permit a better identification-by exploiting the interaction between sectoral wage growth (exogenous to the firm) and the lagged labor share of the firm. A 1 percent increase in real wages is estimated to cause a 1/3 percent fall in fixed capital. Profits absorb only 1\2 of the cost increase, pointing to the role of liquidity constraints. These results highlight the need for labor market reform to reinvigorate investment, and thus labor productivity and job creation.